Implementation of Project-Based Learning Model in Lisadanur Program to Improve Elementary School Students' Literacy and Numeracy - Siti Toifatun Khasanah; Ana Fitrotun Nisa; Akbar Al Masjid; Sukiyanto Sukiyanto; Heri Maria Zulfiati (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Nahdlatul Wathan Mataram, 2025)
This study aims to analyze the effectiveness of project-based learning implementation through the Lisadanur program in improving elementary school students' literacy and numeracy skills. The study used a quantitative approach with a descriptive-comparative design on student learning outcomes before and after the program implementation. The subjects were elementary school students involved in contextual project-based learning activities that integrated reading, writing, data processing, and numerical problem solving. Data were collected through literacy and numeracy tests and documentation of learning outcomes, then analyzed using descriptive statistical techniques to compare changes in score achievement. The results showed a significant increase in both aspects, namely literacy increased from an average score of 55 to 88.89 and numeracy from 35 to 77.78. These findings indicate that project-based learning can increase student engagement, conceptual understanding, and the ability to apply knowledge in real contexts. In addition, collaborative interactions and the role of teachers as facilitators also support the creation of a meaningful learning environment. Thus, the implementation of the project-based learning model in school programs can be a strategic alternative to strengthen literacy and numeracy competencies in elementary education and support the development of sustainable innovative learning practices